Public debt sustainability and the participation of the new member states in the euro area - Stanek, Piotr (Economics and Business Review, 2014)
The recent financial and economic crisis pushed the ratio of public debt to GDP in a number of industrialised countries to unprecedented levels. This phenomenon was especially marked in the peripheral countries of the euro area, which questioned again the adequacy of the institutional framework of the Economic and Monetary Union (including the Maastricht criteria related to public finance). Thus, the new entrants and candidates to the euro area must put a deeper emphasis on the interrelations between public debt sustainability and participation in the monetary union. The article analyses empirically the interrelationships between the participation of the EU-10 countries in the euro area and the sustainability of their debts. The principal method of investigation is the use of panel stationarity tests. The results, contrary to intuition, indicate no significant differences between countries in the euro area and those remaining outside. (original abstract)